2020
DOI: 10.1039/d0ra04585c
|View full text |Cite
|
Sign up to set email alerts
|

Substituted adenine quartets: interplay between substituent effect, hydrogen bonding, and aromaticity

Abstract: Substituent effects on hydrogen bonds in adenine quartets and aromaticity of adenine rings depend on the quartet type. A4-N3 and A4-N7 quartets are more responsive to the electronic nature of substituents than A4-N1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Comparison of HOMA5 and HOMA6 values for the substituted adenine monomers (with NO 2 , Cl, F, H, Me, NH 2 ) with their values for adenine tetramers (A 4 ) clearly shows that π-electron system of the five-membered rings is almost not affected during the tetramer formation, in contrast to π-electron system of the six-membered rings. 103 Among different types of adenine quartet, aromaticity of both adenine rings in A 4 -N3 tetramer (Scheme 8) is more sensitive to electronic nature of the substituents than in other tetramers. In general, to increase aromaticity of the five-membered rings the electron-accepting substituents should be introduced at the C2 or C8 positions, or the electron-donating substituent at the N9 position.…”
Section: Quartetsmentioning
confidence: 99%
“…Comparison of HOMA5 and HOMA6 values for the substituted adenine monomers (with NO 2 , Cl, F, H, Me, NH 2 ) with their values for adenine tetramers (A 4 ) clearly shows that π-electron system of the five-membered rings is almost not affected during the tetramer formation, in contrast to π-electron system of the six-membered rings. 103 Among different types of adenine quartet, aromaticity of both adenine rings in A 4 -N3 tetramer (Scheme 8) is more sensitive to electronic nature of the substituents than in other tetramers. In general, to increase aromaticity of the five-membered rings the electron-accepting substituents should be introduced at the C2 or C8 positions, or the electron-donating substituent at the N9 position.…”
Section: Quartetsmentioning
confidence: 99%
“…[29] Recently, Rodgers et al, [30] have also shown that 5-methylation on protonated cytidine dimers increases its hydrogen bonding energy. Besides, Szatylowicz et al [31] have analyzed the effects of substituents like NO 2 , Cl, F, H, CH 3 , and NH 2 in three remote positions of adenine and its three cyclic tetramers. In one of their complexes with a nitro group, they have also shown that the presence of side weak interactions can increase the stability of the quartet.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rodgers et al., [30] have also shown that 5‐methylation on protonated cytidine dimers increases its hydrogen bonding energy. Besides, Szatylowicz et al [31] . have analyzed the effects of substituents like NO 2 , Cl, F, H, CH 3 , and NH 2 in three remote positions of adenine and its three cyclic tetramers.…”
Section: Introductionmentioning
confidence: 99%
“…The aromaticity of cyclic structures is a key parameter for their reactivity. , Aromatic rings show diamagnetism and increase the stability of the structures. In contrast, antiaromatic rings show paramagnetism and less stability.…”
Section: Introductionmentioning
confidence: 99%